Del “Arte de marear” a la navegación astronómica: Técnicas e instrumentos de navegación en la España de la Edad Moderna - González González, Francisco José (Cuadernos de Historia Moderna, 2006)
Spain’s seamanship innovations in the Modern Era bore a direct relationship to the political and economic development of the modern state by the Catholic Monarchs. The expansion stage of the great discoveries coincided with the writing of the great C16th treatises on the art of navigation and also with the continual honing of the methods and instruments designed in the last part of the Middle Ages. In the seventeenth century navigation suffered along with everything else as Spain slumped into a deep crisis, losing touch with the mainstream political and scientific developments elsewhere in Europe. Lastly came the upturn in the Century of Enlightenment, characterised by economic buoyancy and the maritime control policy brought in by the new Bourbon dynasty; this led to another burst of Spanish contributions to navigation science, especially in the last third of the century.